Environmental Geological Condition and Ground Water Bearers Relationship on Kebakalan Area, Kebumen - East Java - Nandian Mareta; Edi Hidayat (Natural B, Journal of Health and Environmental Sciences, 2016)
Kebakalan and sorrounding included in area of Karangsambung Geological Natural Preservation (CAGK). As part of CAGK, geology Kebakalan and sorrounding area including Luk Ulo Melange Complex age Pre Tertiary expose in Java. These rocks are composed of scaly clay matrix with component in the form of block of igneous, sedimentary and metamorphic rocks. Many human activities is never separated from water using. These condition make that a region can maintain the quality and quantity of water resources. Avalaibility water resources of an area should be able to meet the water needs to water expected so balancing of two is happened. Rapid population growth in Kebakalan can increase needs for water resources for fullfillment of their needs. Water resources consist of surface and subsurface water (groundwater). The main purpose of these study is to determine the relationship between geology and groundwater conditions in Kebakalan and sorrounding an effort to overcome the droughts that frequently hit the area. The research method used two approaches that are primary and secondary data collection. The results showed there were eight units of geologic environments, in which two units are units hills sloping sandstone and alluvium plains unit is a good rock as aquifers. While the direction of groundwater flow from north to south with a depth of 4-8 m wells and groundwater levels 55-70 m. The villages that have potential for shallow ground water is Kedungnangka, Jambekerep, Jombor Kidul, Polaman, Panunggalan, Kebakalan and Gagakbaning with an area 462 ha (44%).